Alternatives to glucocorticoid monotherapy in the treatment of polymyalgia rheumatica. Issue 12 (9th December 2022) - Walz, Kirsten; Elliott, Lydia; Pearson, Tamera
Abstract : Supplemental Digital Content is Available in the Text. ABSTRACT: Background: Treatment of polymyalgia rheumatica (PMR) can be challenging. The most efficacious and cost-effective treatment of PMR is some type of glucocorticoid (GC), with necessary treatment duration typically one year or longer. This duration of GC use is often associated with significant morbidity. Numerous studies have been and are being conducted that focus on alternative treatment modalities. Objectives: This literature review explores alternatives to glucocorticoid monotherapy in the treatment of PMR. Data Sources: An integrative literature review was conducted to evaluate peer-reviewed literature on the topic. An electronic literature search was performed in the Cochrane Database of Systematic Reviews, and an EBSCO search identified relevant articles in the following databases: MEDLINE Complete, Academic Search Premier, Cumulative Index of Nursing and Allied Health (CINAHL) Plus, PsycInfo, Education Source, SocINDEX, the CDC, and PubMed. Conclusions: Agents such as methotrexate and tocilizumab have been used successfully in conjunction with oral glucocorticoids and have demonstrated steroid-sparing effects. A promising adjunctive treatment is the monoclonal antibody, tocilizumab, which has been studied as both adjuvant and monotherapy. Further research in the efficacy, safety, and affordability of these agents is warranted. Implications for Practice: Because PMR is commonly diagnosed and managed in primary care, providers should keep abreast of the most current recommendations concerning optimal treatment options and carefully weigh the risks versus benefits of long-term GC use. This expanding area of research may assist primary care providers to better treat and manage PMR as well as reduce long-term treatment risk by minimizing corticosteroid use when possible.